2021
DOI: 10.3389/fnut.2021.762753
|View full text |Cite
|
Sign up to set email alerts
|

Do Certain Flavonoid IMPS Have a Vital Function?

Abstract: Flavonoids are a vast group of metabolites that are essential for vascular plant physiology and, thus, occur ubiquitously in plant-based/-derived foods. The solitary designation of thousands of known flavonoids hides the fact that their metabolomes are structurally highly diverse, consist of disparate subgroups, yet undergo a certain degree of metabolic interconversion. Unsurprisingly, flavonoids have been an important theme in nutrition research. Already in the 1930s, it was discovered that the ability of syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…Numerous epidemiological studies have shown that a diet rich in flavonoids decreases the risk of developing neurodegenerative diseases, including PD (4,8,11,(14)(15)(16)36). Neuroprotective activity of several flavonoids has also been proven in numerous animal studies, however, the molecular mechanism of action of these compounds remains elusive (2,12). It also remains unknown whether all classes of flavonoids are characterized by similar neuroprotective activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous epidemiological studies have shown that a diet rich in flavonoids decreases the risk of developing neurodegenerative diseases, including PD (4,8,11,(14)(15)(16)36). Neuroprotective activity of several flavonoids has also been proven in numerous animal studies, however, the molecular mechanism of action of these compounds remains elusive (2,12). It also remains unknown whether all classes of flavonoids are characterized by similar neuroprotective activity.…”
Section: Discussionmentioning
confidence: 99%
“…A score of epidemiological studies strongly points to the fact that lifestyle modifications such as regular physical activity and/or following certain types of diet, such as the Mediterranean diet, have been linked to a lower risk of developing Alzheimer's (AD) or Parkinson's disease (PD) (3)(4)(5)(6)(7)(8)(9)(10)(11). Bioactive compounds, often referred to as specialized (or secondary) metabolites abundant in plant-rich diets, have been linked to beneficial and disease-preventive effects of dietary approaches (12). Polyphenols belong to a class of abundant specialized metabolites that have been often considered as majorly responsible for the beneficial effects of plant-based diets (2,12,13).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations